2006
DOI: 10.1007/s11090-006-9008-4
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Effect on Toluene Decomposition in a Wire-plate Dielectric Barrier Discharge Reactor

Abstract: Laboratory-scale experiments were performed to evaluate the humidity effect on toluene decomposition by using a wire-plate dielectric barrier discharge (DBD) reactor at room temperature and atmospheric pressure. The toluene decomposition efficiency as well as the carbon dioxide selectivity with/without water in a gas stream of N 2 with 5% O 2 was investigated. Under the optimal humidity of 0.2% the characteristics of toluene decomposition in various background gas, including air, N 2 with 500 ppm O 2 , and N 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…According to the reaction constanants, OH radicals play an important role in the destruction of HCHO as compared to ozone. The same study for removal of 50 ppm toluene in a DBD reactor showed that despite the positive role of presence of water molecules in the formation of OH radicals, increasing the relative humidity level (up to 80%) has negative effect on the removal efficiency due to decreasing electron density and quenching the reactive species in the reactor . Therefore, humidity level plays a crucial role on the removal performance of the NTP reactors.…”
Section: Non‐thermal Plasma (Ntp)mentioning
confidence: 95%
See 2 more Smart Citations
“…According to the reaction constanants, OH radicals play an important role in the destruction of HCHO as compared to ozone. The same study for removal of 50 ppm toluene in a DBD reactor showed that despite the positive role of presence of water molecules in the formation of OH radicals, increasing the relative humidity level (up to 80%) has negative effect on the removal efficiency due to decreasing electron density and quenching the reactive species in the reactor . Therefore, humidity level plays a crucial role on the removal performance of the NTP reactors.…”
Section: Non‐thermal Plasma (Ntp)mentioning
confidence: 95%
“…Relative humidity has an important role in plasma catalyst performance . Yu‐fang et al studied the effect of humidity on toluene decomposition efficiency in a PPC reactor at the ambient temperature. The result of carrying their experiments in the presence of Co 3 O 4 /Al 2 O 3 /nickel foam as catalyst showed the importance role of water molecules in completing the oxidation reactions.…”
Section: Plasma Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…One way, which has been developed extensively, to overcome these disadvantages is by placing a catalyst inside or post discharge. Depending on the VOC chemical structure, nonthermal plasma reactor layout and catalyst chemical nature, several conclusions were drawn in respect of VOC removal efficiency (RE), ozone concentration, carbon mass balance (CMB), by-products selectivites, specific energy or discharge behavior [4][5][6][7][8][9][10][11][12][13][14]. Treatment by non thermal plasma alone succeeds in removing low concentration pollutants at low energy consumption compared to conventional catalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…In a plasma alone configuration, when no catalyst was present in the discharge or post discharge, opposite effects were observed depending on the relative humidity (RH) percentages present in the gas stream [4,7,12,13]. In a low humid environment, the formation of highly oxidative hydroxyl radicals ( • OH) increases due to the dissociation of water molecules by impact with electrons or oxygen radicals, O(1D).…”
Section: Introductionmentioning
confidence: 99%